2015
DOI: 10.1002/chem.201405405
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of the High Spin→Low Spin Relaxation Dynamics of the Porous Coordination Network [Fe(pz)Pt(CN)4]⋅2.6 H2O

Abstract: The Hoffman-type coordination compound [Fe(pz)Pt(CN)4]⋅2.6 H2O (pz = pyrazine) shows a cooperative thermal spin transition at around 270 K. Synchrotron powder X-Ray diffraction studies reveal that a quantitative photoinduced conversion from the low-spin (LS) state into the high-spin (HS) state, based on the light-induced excited spin-state trapping effect, can be achieved at 10 K in a microcrystalline powder. Time-resolved measurements evidence that the HS→LS relaxation proceeds by a two-step mechanism: a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…We have shown that clustering starts from corners or edges and that the dependence of the shape of the sample is essential for the macroscopic properties. We have proposed a method of scanning the sample, which could be useful not only for discussing various simulations, but also to help understand experimental xray powder-diffraction data as, for example, those obtained recently in the case of porous coordination networks [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that clustering starts from corners or edges and that the dependence of the shape of the sample is essential for the macroscopic properties. We have proposed a method of scanning the sample, which could be useful not only for discussing various simulations, but also to help understand experimental xray powder-diffraction data as, for example, those obtained recently in the case of porous coordination networks [29].…”
Section: Discussionmentioning
confidence: 99%
“…5); (iii) for each step we calculate the average HS fraction in the cube and obtain a histogram for the number of cubes for a given HS fraction. Such a histogram can be interpreted as being a direct representation of the evolution of an x-ray powder-diffraction diagram during the thermal spin transition or the HS-LS relaxation, which provide information both on the dynamics and on the structural parameters, following the position, width, and intensity of the peaks [27][28][29]. Another method to obtain like-diffraction peaks for the simulations has previously been proposed by Nicolazzi et al [30], but it implied the calculation of the distances between all molecules in the system, whereas the present method could be applied even for systems for which the volume does not vary during transition.…”
Section: Methods To Study the Evolution Of Clustersmentioning
confidence: 99%
“…The transduction mechanism is expected to have the same origin as for the thermal spin transition, and is presumably related to the SCO transition following a nucleation-growth dynamics at the macroscopic bulk-like length scale expected for the thin film prepared here. [59] The reverse-LIESST experiments are performed by illuminating the device with near-infrared light (λ 2 = 820 nm, 100 µW.mm -2 , 5 T 2g  5 E g transition). We observe an inverse change of the graphene conductance compared to the LIESST effect (Figure 3a), which indicates that a fraction of the HS species has been successfully reconverted into the LS state.…”
Section: Resultsmentioning
confidence: 99%
“…With this respect, the observation of the smooth evolution preceding the steeper one in the two branches of the hysteresis loop might be a consequence of the large distribution of the size of the nanocrystals forming the film (AFM images Figure 1c and Figure S2) and thus, the convolution of a slow non-cooperative relaxation (random spin-mixing, small-enough nanocrystals) with the cooperative one (clusters). [59,62] Further studies are required for characterizing the dynamics, [63] and its size-dependence, [59,62] for evaluating the role of the interface of the SCO layer, [42,64] and within the layer, the inter nanocrystals effect. The thermal and light induced SCO described and discussed above demonstrate the ability of the device to sense the macroscopic changes of the film despite the mere interfacial contact with graphene.…”
Section: Resultsmentioning
confidence: 99%
“…Delagado et al used synchrotron kinetic powder X-ray diffraction to probe the structural distortion and reorganization accompanying the lightinduced and relaxation spin transitions at cryogenic temperature. 127 The relaxation process after light excitation shows a complex kinetics. Initially, the light-induced diffraction pattern corresponds to a pure HS phase.…”
Section: The X-ray Diffraction Pattern Under T Perturbation and Photo-excitationmentioning
confidence: 99%